Inovasi Pembelajaran Berbasis Teknologi Artificial Intelligence (AI) Ditinjau melalui Perspektif Alkitabiah - Nawa, Anandha Glorrys Graceia; Gunanto, Yohanes Edi (Universitas Pelita Harapan, 2025)
Modern developments have had a significant influence on the world of education, for example technology-based learning innovations. However, technological developments have both positive and negative impacts. An examination based on a Biblical perspective is sufficient to answer the problems that arise because it is important to view the presence of technology as God's providence that must be used wisely. If not reviewed biblically, the presence of technology becomes a big problem in learning. The purpose of writing this paper is to present a study of Christian philosophy and theology regarding learning innovations based on Artificial Intelligence (AI) technology. Educational innovation based on AI technology in the perspective of Biblical Christian insights using the research method of literature review. Hopefully God's providence will be manifested in learning practice that glorify God and the world's philosophical views will not shake Christian faith. The results of the discussion show the philosophical views and Christian theology that students will get from teachers who invite students to properly examine AI technology-based learning innovations. The conclusion is that technology-based learning innovations are designed by Christian teachers in accordance with God's will. Suggestions that Christian teachers can make in learning are to deepen their mastery of knowledge, skills and correct attitudes regarding technological developments.